Comparison between Flexible Collagen and Vein Conduits Used for Size-Discrepant Nerve Repair: An Experimental Study in Rats - Demir, Ahmet; Simsek, Tekin; Acar, Murat; Aktaş, Abit; Vlamings, Rinkse; Ayyıldız, Mustafa; Yıldırım, Mehmet; Temel, Yasin; Kaplan, Süleyman (Journal of Reconstructive Microsurgery, 2014)
Primary nerve repair is the gold standard in nerve reconstruction. When primary repair is not possible for injured nerves, conduit-assisted repair methods are frequently used. As conduits, autologous vein segments or allogenic biodegradable products can be used. However, their effectiveness when used in a nerve defect where a size discrepancy exists has not been compared. In this study, either a vein graft or a synthetic collagen conduit was used to bridge 10-mm defects between size-discrepant tibial and peroneal nerves in a rat model. After 90 days, nerve regeneration was evaluated using electrophysiological and histological methods. It can be concluded based on the results of this study that bridging a 10-mm nerve gap with synthetic collagen conduits and autologous vein grafts yielded similar results in small-to-large nerve coaptations, with the vein graft being slightly more effective.
Keywords: size discrepancy; collagen conduit; vein conduit